Meta-analysis of bacterial meningitis score validation studies. Issue 9 (4th July 2012) - Nigrovic, Lise E; Malley, Richard; Kuppermann, Nathan
Abstract : Objective: The Bacterial Meningitis Score, a derived and validated clinical decision rule, identifies children with cerebrospinal fluid (CSF) pleocytosis who are at very low risk of bacterial meningitis. Low-risk features include the following: negative CSF Gram stain, CSF absolute neutrophil count (ANC) <1000 cells/μl, CSF protein <80 mg/dl, peripheral blood ANC <10 000 cells/μl and no seizure at or prior to initial presentation. The study objective of the present work was to calculate the performance of the Bacterial Meningitis Score by performing a meta-analysis of all published validation studies. Methods: A meta-analysis of all studies published between 2002 and 2012 was performed, evaluating the performance of the Bacterial Meningitis Score in children with CSF pleocytosis. Study quality was assessed using the assessment of diagnostic accuracy studies instrument and then the test performance of the prediction rule was calculated. Results: From 8 studies, 5312 patients were identified, of whom 4896 (92%) had sufficient clinical data to calculate the Bacterial Meningitis Score. Bacterial meningitis was diagnosed in 1242 children (23% of study patients). The combined sensitivity of the Bacterial Meningitis Score for bacterial meningitis was 99.3% (1224/1233; 95% CI 98.7% to 99.7%), specificity 62.1% (2274/3663; 95% CI 60.5% to 63.7%) negative predictive value 99.7% (2274/2283, 95% CI 99.3% to 99.9%), positive likelihood ratio 2.6 (95% CI 2.5 to 2.7) and negative likelihood ratio 0.01 (95% CI 0.01 to 0.02). Conclusions: The Bacterial Meningitis Score is a highly accurate clinical scoring system that could be used to assist clinical decision making for the management of children with CSF pleocytosis.